Extraction of titanium(IV) from aqueous hydrochloric acid solutions into alamine 336-m-xylene mixtures - (:unkn) unknown (TAYLOR & FRANCIS INC, 2006)
Extraction of Ti(IV) from its aqueous hydrochloric acid solutions into organic Alamine 336-m-xylene systems was investigated. Extraction experiments were conducted with three different initial metal concentrations of 1, 3, and 6 mg/mL, each at three acidic molarities of 1, 5, and 10 M. It was observed that the extractability of Ti(IV) increases with increasing acidic molarities. Alamine 336 diluted with m-xylene was found to be a suitable extractant for Ti(IV) across this acidic range. In parallel, a mathematical model was developed to correlate metal extractability and Alamine 336 volume content. Optimal Alamine 336 contents were estimated for single-stage extraction.
Keywords: Ti(IV) extraction; Alamine 336; model; LIQUID-LIQUID-EXTRACTION; CHAIN ALKYL AMINES; GROUP VIII METALS; SOLVENT-EXTRACTION; CHLORIDE SOLUTIONS; SULFATE-SOLUTIONS; SEPARATION; IRON(III); EQUILIBRIA; MOLYBDENUM